Hebbian Optocontrol of Cross-Modal Disruptive Reading in Increasing Acoustic Noise in an Adult with Developmental Coordination Disorder: A Case Report - Albert Le Floch; Guy Ropars (Brain Sciences)
Acoustic noise is known to perturb reading for good readers, including children and adults. This external acoustic noise interfering at the multimodal areas in the brain causes difficulties reducing reading and writing performances. Moreover, it is known that people with developmental coordination disorder (DCD) and dyslexia have reading deficits even in the absence of acoustic noise. The goal of this study is to investigate the effects of additional acoustic noise on an adult with DCD and dyslexia. Indeed, as vision is the main source of information for the brain during reading, a noisy internal visual crowding has been observed in many cases of readers with dyslexia, as additional mirror or duplicated images of words are perceived by these observers, simultaneously with the primary images. Here, we show that when the noisy internal visual crowding and an increasing external acoustic noise are superimposed, a reading disruptive threshold at about 50 to 60 dBa of noise is reached, depending on the type of acoustic noise for a young adult with DCD and dyslexia but not for a control. More interestingly, we report that this disruptive noise threshold can be controlled by Hebbian mechanisms linked to a pulse-modulated lighting that erases the confusing internal crowding images. An improvement of 12 dBa in the disruptive threshold is then observed with two types of acoustic noises, showing the potential utility of Hebbian optocontrol in managing reading difficulties in adults with DCD and dyslexia.